ABOUT THE NEED TO EXTEND THE REACH OF THE PROHIBITION OF THE ABUSE OF RIGHTS - Radulović, Srđan M (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The legal institute that prohibits abuse of rights is an exception to the rule that the question of someone’s civil liability shall be asked only if legal subject acted contrary to the legal norm or, rarely, non-legal norm. Being so, most basic logical rule when interpreting this legal institute is to interpret norms which constitute it in narrowest possible sense. Nevertheless, research that preceded this paper shows the necessity to extend effects of this legal institute in order to cover all those situations in which legal subject remained passive when it comes to use its civil rights. In that sense – relying heavily on the advantages of normative method, teleological interpretation and multidisciplinary approach – the author emphasizes relative nature of obligations and examines, not how the legal institute that prohibits abuse of rights functions in civil procedural law, but the need to construct this legal institute in next civil code exactly as in the procedural law.